English Masculinities, 1660-1800. - Hitchcock, Tim (Women and men in history., 2014)
This collection of specially commissioned essays provides the first social history of masculinity in the 'long eighteenth century'. Drawing on diaries, court records and prescriptive literature, it explores the different identities of late Stuart and Georgian men. The heterosexual fop, the homosexual, the polite gentleman, the blackguard, the man of religion, the reader of erotica and the violent aggressor are each examined here, and in the process a new and increasingly important field of historical enquiry is opened up to the non-specialist reader. The book opens with a substantial introd.